Construction of chitooligosaccharide-based nanoparticles of pH/redox cascade responsive for co-loading cyclosporin A and AZD9291. (1st September 2022) - Chen, Shumin; Ji, Xiaoguo; Zhao, Mengyao; Jin, Jiayang; Zhang, Haiping; Zhao, Liming
Abstract: AZD9291 can prolong the survival of patients with non-small cell lung cancer. Unfortunately, resistance to AZD9291 is inevitable and hinders effectiveness. Studies showed the combination of Cyclosporin A (CsA) and AZD9291 could increase the efficacy of AZD9291, but the delivery efficiency of free drugs was limited. A chitooligosaccharide (COS) -based nanoparticle with enhanced delivery efficiency and endocytosis was constructed in this study. The results showed that this pH/redox cascade responsive nanoparticles improved therapeutic effect. The system is small and the surface charge changed from negative to positive according to the weakly acidic tumor microenvironment. After endocytosis, the nanoparticles decomposed and released AZD9291 and CsA in redox-rich cytoplasm. Experiments in vitro and in vivo proved that the nanoparticles overcame the biological barrier and significantly enhanced the anti-tumor effect of AZD9291. The novel multifunctional nanoparticle provides a way to overcome the drug resistance and the possibility of clinical application. Graphical abstract: Unlabelled Image